Isentropic transport and the seasonal cycle amplitude of CO2. Issue 13 (12th July 2016) - Barnes, Elizabeth A.; Parazoo, Nicholas; Orbe, Clara; Denning, A. Scott
Abstract: Carbon‐concentration feedbacks and carbon‐climate feedbacks constitute one of the largest sources of uncertainty in future climate. Since the beginning of the modern atmospheric CO2 record, seasonal variations in CO2 have been recognized as a signal of the metabolism of land ecosystems, and quantitative attribution of changes in the seasonal cycle amplitude (SCA) of CO2 to ecosystem processes is critical for understanding and projecting carbon‐climate feedbacks far into the 21st Century. Here the impact of surface carbon fluxes on the SCA of CO2 throughout the Northern Hemisphere troposphere is investigated, paying particular attention to isentropic transport across latitudes. The analysis includes both a chemical transport model GOES‐Chem and an idealized tracer in a gray‐radiation aquaplanet. The results of the study can be summarized by two main conclusions: (1) the SCA of CO2 roughly follows surfaces of constant potential temperature, which can explain the observed increase in SCA with latitude along pressure surfaces and (2) increasing seasonal fluxes in lower latitudes have a larger impact on the SCA of CO2 throughout most of the troposphere compared to increasing seasonal fluxes in higher latitudes. These results provide strong evidence that recently observed changes in the SCA of CO2 at high northern latitudes (poleward of 60°N) are likely driven by changes in midlatitude surface fluxes, rather than changes in Arctic fluxes. Key Points: The seasonal cycle amplitude (SCA) of CO2 roughly follows isentropic surfaces Changes in lower‐latitude seasonal fluxes impact the SCA more than changes in higher‐latitude fluxes The seasonality of the circulation can account for 10–20% of the SCA of an idealized CO2 tracer